PENERAPAN METODE COOPRATIVE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) DI SMPN - 2 HANAU - Mulyani, Mulyani (Jurnal Aplikasi Manajemen Pendidikan, 2014)
Islamic Education (PAI) has ore value in the cultivation of the values and character of the learners. Islamic education is the cornerstone of character development of students. Improving the quality of Islamic education in schools is intended as an effort to achieve goals through increased PAI minimum standards of achievement in the subject of PAI in the cognitive and psychomotor. Learning in the Education Unit Level Curriculum (SBC) requires the active participation of all students. So in the prosess of learning, student-centered activities, the teacher’s role as motivator an facilitator only it is cooperative learning. In cooperative learning activities of students during script really empower students to actualize the potential of knowledge an dkills, so it really fits with the constructivist approach develoved at this time.In cooperative learning, students are trained to be able to work together and recognize differences of opinion with other people. Of some kinds of models of cooperative learning, cooperative learning model used in the script is very precise and PAI learning as a strategy to improve student learning outcomes PAI. Cooperative script is a learning model that conditioned student to work in pairs and verbally summarize the parts of the material being studied. Analysis of the data used is a different test pairs of data it can be concluded that the use of learning using cooperative learning methods of students more active script and understand the subject matter. Students are also more willing to as the teacher, it is supported by a fun learning atmosphere, compared with conventional models, students are less active and the students seem less enthusiastic in participating in learning.